Error pattern measurement and analysis in wireless communication (Software development) - Muhammad Afham bin Sidik (2023)
Wireless Sensor Network (WSN) is introduced as a network which has autonomous sensors in order to monitor some physical and environmental conditions like temperature, pressure and etc. It has been become quickly to take care of the perpetually expanding demand. WSN is aimed to achieve the development of low data rate, low power consumption and low cost wireless networking and it has improved the performance of automation field too.